Taijiquan and Daoism. From Religion to Martial Art and Martial Art to Religion (Revista de Artes Marciales Asiáticas, 2012)
This study explores the ways in which the construction and deconstruction of a martial arts-Daoism connection has figured in political ideology, national iden-tity, and commercial interest during the past 400 years of Chinese history. Focusing on the taijiquan-Daoism-Zhang Sanfeng nexus, it traces the wrapping of a martial art in indigenous religious garb during the periods of Manchu rule, Japanese occupation, and post-Mao 21st century. It concludes by reporting on a contemporary movement in China to revive the cult of Zhang Sanfeng and to cast taijiquan as a form of religious practice. In this light, taijiquan emerges as an important site of constructing “Chinese-ness” in the face of state appropriation and Western cultural imperialism.